Determinasi Internal & Peran Ownership Concentratation Atas Profitabilitas Bank Perkreditan Rakyat (Di Kota Semarang) - Paulus Wardoyo; Sri Purwantini; Endang Rusdianti (Politeknik Ganesha Medan, 2023)
Rural Banks in Indonesia are facing problems regarding the health of their performance in recent years which shows a flat trend. Even the City of Semarang from 2019 to 2021 shows an average downward trend. In addition to the research results that are inconsistent between Non Performing Loans and Net Interest Margin on profitability or Return On Assets, this study aims to examine the role of Ownership Concentration as a moderating variable used to solve these problems. This study uses secondary data from 25 conventional BPRs that have their head office in Semarang City for the observation period 2016 – 2021. The sampling technique used is purposive sampling. Data analysis uses SPSS software. The Source of data for Rural Bank financial reports can be accessed on the website of the Financial Services Authority. The results showed that Net Interest Margin had a positive effect on profitability, whereas Non-Performing Loans hurt profitability. Ownership Concentration can moderate the effect of Non-Performing Loans on the level of profitability, but not the Net Interest Margin. The results of this study prove that Ownership Concentration will always strive to protect the interests related to its investment. The purpose of this study was to examine the role of ownership concentration as a moderating variable used to resolve the research gap on the effect of NPL and NIM on BPR profitability. This study uses conventional BPR respondents who have a head office in Semarang City, totaling 25. This study uses a purposive sampling technique. The results showed that NIM had a positive effect on the profitability of BPR, on the contrary, NPL had a negative influence. In addition, ownership concentration was able to moderate the effect of NPL on profitability, but not on NIM. This study proves that the ownership concentration will always try to protect the interests related to its investment. Further research can be done by expanding the coverage area under study and increasing the number of respondents, or it can also be done in other industries.